2002
DOI: 10.1021/ol026923b
|View full text |Cite
|
Sign up to set email alerts
|

UCS1025A and B, New Antitumor Antibiotics from the Fungus Acremonium Species

Abstract: [structure: see text] UCS1025A and B, novel pentacyclic polyketides with an unprecedented furopyrrolizidine skeleton, were isolated from the fungus Acremonium sp. KY4917. The structures and stereochemistry were elucidated by a combination of two-dimensional NMR and X-ray crystallographic analysis. UCS1025A showed unique chemical equilibria involving three tautomeric isomers and exhibited antimicrobial activity and antiproliferative activity against human tumor cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 14 publications
1
46
0
1
Order By: Relevance
“…Some secondary metabolites that contain the deoxy-tetramic acid ring system have been reported, such as oteromycin, [6] ZG-1494a, USC1025A and B, [8,9] pyrrocidines A and B, [10] ascosalipyrrolidinones A and B, [11] and talaroconvolutins A-D. [12] Although the biogenetic pathways of 1-5 and the deoxy-tetramic acid related compounds mentioned above remain unclear, a plausible pathway can be proposed. This pathway is based on the biosynthetic route of the tetramic acid analogue, trichosetin, and involves a polyketide reacting with one amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…Some secondary metabolites that contain the deoxy-tetramic acid ring system have been reported, such as oteromycin, [6] ZG-1494a, USC1025A and B, [8,9] pyrrocidines A and B, [10] ascosalipyrrolidinones A and B, [11] and talaroconvolutins A-D. [12] Although the biogenetic pathways of 1-5 and the deoxy-tetramic acid related compounds mentioned above remain unclear, a plausible pathway can be proposed. This pathway is based on the biosynthetic route of the tetramic acid analogue, trichosetin, and involves a polyketide reacting with one amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Besides being abundant throughout nature,i zidine alkaloids are also of considerable importance owing to their potent and diverse biological activities. [11] Furthermore,the high and subtype-selective affinity for the nicotinic acetylcholine receptor, [7a,9,12] as well as the positive modulation of voltage-dependent sodium channels, [13] renders them potential candidates for the treatment of various important CNS disorders, [14] or as cardiotonic drugs, [13] respectively. Many of these compounds have been shown to exhibit potent antitumor properties and/or antimicrobial activities.…”
mentioning
confidence: 99%
“…KY4917 by Yamashita et al in 2000, [1] was shown to inhibit telomerase and have antimicrobial activity. [2] This remarkable biological activity coupled with its highly complex structure makes 1 an attractive target for total synthesis; several synthetic studies on this family of compounds have been published. [3] Three total syntheses have been reported to date: these were by the groups of Danishefsky, [4] Hoye, [5] and Christmann.…”
mentioning
confidence: 99%